1985
DOI: 10.1001/archotol.1985.00800070057007
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian Tube Function in the Chinchilla

Abstract: \s=b\Eustachian tube function (ETF) was evaluated in 22 ears of 18 chinchillas using the inflation-deflation and forcedresponse protocols. The results of the ETF tests showed an unusual function in the chinchilla. Of the 22 tests, one indicated a patulous eustachian tube (ET) and 20 suggested a semipatulous ET. This was evidenced by a passive, pressure\x=req-\ dependent, complete reduction of applied positive or negative ME pressures in these ears. This phenomenon has no counterpart in the ETF of rhesus monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…1° However, normal tubal function in the chinchilla is quite different from that in ferrets and human beings, making comparison difficult. 12 The fact that OM was not seen in this study is in contrast to findings reported for previous human viral challenges. Although uncommon, OM has been observed in a small proportion of adult volunteers experimentally infected with rhinovirus-39 (3%) 5 and influenza A virus (19%).…”
Section: Discussloncontrasting
confidence: 90%
“…1° However, normal tubal function in the chinchilla is quite different from that in ferrets and human beings, making comparison difficult. 12 The fact that OM was not seen in this study is in contrast to findings reported for previous human viral challenges. Although uncommon, OM has been observed in a small proportion of adult volunteers experimentally infected with rhinovirus-39 (3%) 5 and influenza A virus (19%).…”
Section: Discussloncontrasting
confidence: 90%
“…Three mechanisms could lead to the transfer of a unilaterally applied substance to the contralateral inner ear. One is transmission via the Eustachian tube, which is continuously open in the chinchilla model (Doyle, 1985). This mode of transmission is less likely, as transfer to the contralateral ear occurs with micropump application of gentamicin to the round window at low rates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that gas exchange can occur both into and out of the middle ear cavity via the eustachian tube and also by passive diffusion across the middle ear mucosa (22,53). Furthermore, the chinchilla eustachian tube appears to be continually semipatulous where a constant airflow may be maintained by the passage of air into the middle ear cleft (15). The presence of an air-fluid interface in the chinchilla bulla 7 days after infection still allows gas exchange through the middle ear mucosa (29).…”
Section: Discussionmentioning
confidence: 99%